The British Labour Party and twentieth-century Ireland : The cause of Ireland, the cause of Labour - Marley, Laurence (Book collections on Project MUSE., 2016)
With contributions from a range of distinguished Irish and British scholars, this collection of essays provides a full treatment of the historical relationship between the Labour Party and Ireland in the last century, from Keir Hardie to Tony Blair.